The Narrative Structure of Ambiguity - Rizzo, Luca (Annali di Ca’ Foscari: Serie Orientale, 2018)
This paper engages in a semiotic analysis of a tawriya-epigram by Šihāb al-Dīn b. al-ʿAṭṭār (d. 794/1392). Mamluk literature is renowned for its extended usage of figures of speech, above all the tawriya, ‘double entendre’. The goal of this articole is to shed light on the tawriya, taking into account the Arabic classical theory and presenting a new approach based on semiotics. The subject of my analysis is the most flourishing literary genre of the epoch: the epigram. Within the epigram, the tawriya plays a pivotal role. Its potential is not limited to a twofold reading of the text but rather goes further and creates a second text out from the first, both of which cooperate with one another and shed light upon their respective meanings. Therefore, the epigram by Ibn al-ʿAṭṭār is a construction of several texts, each of which is mutually linked and deeply-rooted in the social and physical environment depicted in the poem: the ḥammām.